Sedation and Analgesia Practices in Pediatric Intensive Care Units: A Survey of 27 Centers from Turkey - Ekinci, Faruk; Yildizdas, Dincer; Horoz, Ozden Ozgur; Aslan, Nagehan; The Society of Pediatric Emergency Intensive Care Medicine of Turkey-Sedoanalgesia Study Group (Journal of Pediatric Intensive Care, 2020)
The management and monitoring of sedoanalgesia are important measures in improving the efficacy of procedures and mechanical ventilation, as well as reducing adverse effects and preventing withdrawal syndrome, and delirium in pediatric intensive care units (PICUs). As there is an ongoing need to clarify the best approach to sedoanalgesia in PICUs, we aimed to analyze the current approaches in sedation, analgesia, withdrawal, and delirium practices among PICUs in Turkey. Twenty-seven PICUs completed the survey. Only 9 (33.3%) and 13 (48.1%) centers had a written protocol for analgesia and sedation, respectively. Paracetamol and a combination of midazolam and fentanyl were preferred in 51.8 and 40% of the PICUs for postoperative periods, respectively, and 81.4% of the units preferred ketamine for short-term interventions. For prolonged sedation in mechanically ventilated children, a combination of benzodiazepines and opiates were the most preferred first-line agents with a very high percentage of 81.4%, whereas ketamine and dexmedetomidine accounted for 62.9 and 18.5%, respectively, as second-line options. Although sedative and analgesic agent preferences were comparable with the relevant literature, we should focus on developing a standardized, evidence-based algorithm for sedation and analgesic drugs.
Keywords: analgesia; delirium; pediatric intensive care; sedation; withdrawal